(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
The article presents the amount of pigment in the leaves of the new Ravot bean variety, the amount of chlorophyll in different phases of its development, and the effect of nitrogen fertilizers on the pigments in the bars.